The domestication of humans - Bednarik, Robert G., author.
1 online resource
Keywords: "The Domestication of Humans explains the alternative to the African Eve model by attributing human modernity, not to a speciation event in Africa but the unintended self-domestication of humans. This alternative account of human origins provides the reader with a comprehensive explanation of all features defining our species that is consistent with all available evidence. These traits include, but are not limited to, massive neotenisation, numerous somatic changes, susceptibility to almost countless detrimental conditions and maladaptations, brain atrophy, loss of oestrus and thousands of genetic impairments. The teleological fantasy of replacement by a 'superior' species that has dominated the topic of modern human origins has never explained any of the many features that distinguish us from our robust ancestors. This book explains all of them in one consistent, elegant theory. It presents the most revolutionary proposal of human origins since Darwin. Although primarily intended for the academic market, The Domestication of Humans is perfectly suitable for anyone interested in how and why we became the species that we are today"--